2006
DOI: 10.1159/000096337
|View full text |Cite
|
Sign up to set email alerts
|

Overactive Bladder Syndrome among Community-Dwelling Adults in Taiwan: Prevalence, Correlates, Perception, and Treatment Seeking

Abstract: Purpose: We investigated the prevalence, correlates, perception of overactive bladder syndrome (OAB) and doctor-consultation behavior among community adults. Subjects and Methods: This urological survey was part of a government-supported health utilization project conducted in Matsu, Taiwan. Participants (n = 1,827) completed a questionnaire collecting information on OAB, which was defined as urgency with either frequency or nocturia. Results: The age-adjusted prevalence of OAB was 16.9%, including 4.5% with u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
4
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 42 publications
2
35
4
3
Order By: Relevance
“…Most other studies have reported greater prevalence of overactive bladder than found in our study [3][10], [14][16]. Some [3][5], [15][17] but not all studies [6] have also reported more urgency incontinence among subjects with overactive bladder than we found.…”
Section: Discussioncontrasting
confidence: 61%
“…Most other studies have reported greater prevalence of overactive bladder than found in our study [3][10], [14][16]. Some [3][5], [15][17] but not all studies [6] have also reported more urgency incontinence among subjects with overactive bladder than we found.…”
Section: Discussioncontrasting
confidence: 61%
“…Overactive bladder (OAB) syndrome is a common condition [1][2][3][4][5] that is associated with a significant negative impact on quality of life. The International Continence Society (ICS) defines OAB as urgency, with or without urgency incontinence, usually with increased daytime frequency and nocturia [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…(2003), частота гМП составляет 16 % у мужчин и 16,9 % у женщин [5]. другая группа исследователей отмечают такую же распространенность гМП среди всех взрос-лых -16,9 % [6]. частота гМП в 16,6 % была выявлена среди 16776 взрослых в общей попу-ляции в 6 европейских странах [7].…”
Section: статья посвящена эпидемиологии гиперактивного мочевого пузырunclassified
“…При этом отме-чено преобладание женщин с гМП в возрасте до 60 лет, в то время как в старшем возрасте частота гМП среди мужчин выше [6,10,14].…”
Section: статья посвящена эпидемиологии гиперактивного мочевого пузырunclassified